2008
DOI: 10.1258/ijsa.2007.007177
|View full text |Cite
|
Sign up to set email alerts
|

The case for social marketing in gonorrhoea prevention: insights from sexual lifestyles in Glasgow genitourinary medicine clinic attendees

Abstract: We conducted a matched case-control study to investigate social factors associated with gonorrhoea acquisition among genitourinary (GU) medicine clinic attendees, designed to inform appropriate prevention strategies. Detailed social and behavioural data were elicited using a self-completed questionnaire. The effect sizes of these characteristics were quantified using univariate and multivariable conditional logistic regression in 53 cases and 106 matched controls. Homo-bisexual orientation was the strongest in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…Other independent risk factors for HIV co-infections in our study were the presence of other STIs (such as syphilis) and having an HIV-positive stable partner, findings that are in line with those from studies in Western Europe [22]. Other authors have indicated that rectal gonorrhoea is an independent risk factor for HIV transmission [9].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other independent risk factors for HIV co-infections in our study were the presence of other STIs (such as syphilis) and having an HIV-positive stable partner, findings that are in line with those from studies in Western Europe [22]. Other authors have indicated that rectal gonorrhoea is an independent risk factor for HIV transmission [9].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, drug and/or alcohol use and sexual contacts under the influence of drugs and/or alcohol were independently associated in our sample with HIV and gonorrhoea co-infections, This relationship has also been reported in other studies in Spain, Great Britain, The Netherlands and Norway [22][23][24][25]. Other independent risk factors for HIV co-infections in our study were the presence of other STIs (such as syphilis) and having an HIV-positive stable partner, findings that are in line with those from studies in Western Europe [22].…”
Section: Discussionsupporting
confidence: 90%
“…Definitions ranged from first sexual partner 39,45 to most recent. 9,13,18,2628,33,36,38,41,46,50,70 Some studies collected information about multiple partners. 10,19,23,26,27,31,39,46,49 Nearly one-third (31%) of studies conducted in middle- and low-income countries but none conducted in high-income countries defined “partner” as the participant’s spouse or enrolled a majority of married participants.…”
Section: Resultsmentioning
confidence: 99%
“…Ten 6,7,18,21,28,30,31,51,52,56 of 11 6,7,18,21,26,28,30,31,51,52,56 studies which investigated race/ethnicity were US-based; 9 of the 10 reported significant findings. 6,7,18,21,28,31,51,52,56 In the 2 prospective studies, an African-American partner was associated with STI acquisition 6,7 In cross-sectional studies, Black or African-American race was positively associated with MG, 18,28 GC, 21 repeat GC 56 and composite STI measures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation